(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Household wastes handling improperly leads to increasing of total amount of wastes deposited in landfills. Investigations of family (3 adults and 3 children) during 3 year period appeared, that average weight of kitchen wastes produced was 62,2 kg per habitant in year. Kitchen wastes have high moisture content 70 – 90% and high density 500 – 600 kg/m³. Investigated weight of liquid leached was 43,2%, if the kitchen wastes were composted without additional material and leakage was 15,4% if wastes was composted together with 10% dry bulking materials (straw5% + sawdust5%). Leakage was not observed, if kitchen wastes were co-composted with 25% lake rootfelt. Maximal temperatures in 1,2 m3 container were 36 °C for compost of weeds and 61 °C for screened weed’s compost. Non-treated with etch wheat grain’s sprouts all perished after 40-day couching period in compost having maximal temperature 36°C during previous composting process and in same time survived 75% of sprouts in compost having maximal temperature 61 °C during previously performed composting process.